Některé spolećné funkce věcných stylů - Čechová, Marie (Stylistyka, 2021)
The author deals with complex „objective” styles (style of science, journalism, administration, and teaching). She gives the definitions of persuasive function and oftwo directive functions (regulative vs. operative function). These functions are -more or less - characteristic for objective styles but are combined in them in different ways, proportions and hierarchies. That is why it is not easy to distinguish between objective styles: they have much in common, we must reckon with overlaps.